Akibat Hukum Terhadap Pembatalan Perkawinan Poligami Terhadap Istri Ke-2 (Dua) - Cahya, Adig; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Marriage is defined as an agreement between men and women to be married. Organizing marriagesin some communities, sometimes ignoring the true will of the candidate who will marry, even in many cases,the future bride and groom will only find out who he will marry with at the time the marriage will take place. It is often the case that marriages take place according to the wishes of the marriage, but are contrary tothe wishes of the other parties, for example the family, both male and female families or polygamousmarriages that are carried out illegally. The consequence of this situation caused no happiness in thehousehold and forced the marriage bond to be decided or canceled. Cancellation of marriage is regulated inarticles 22 up to and including 28 of the marriage law of 1974. Cancellation of polygamous marriage willcause legal consequences and losses for some parties, especially the second ex-wife.The type of research that is used normative legal research, namely research that is carried out byresearch of primary and secondary legal materials. The author conducts research with a view to attractinglegal principles (Rechtsbeginselen) that can be made against written positive legislation and unwrittenpositive legislation. In this study, the author discussed more about the principles of law, in particular theprinciple of justice in the case of the cancellation of the marriage experienced by the second ex-wife . In thiscase to describe the factors, efforts that can be made to seek justice, and legal protection for the second exwifewho is not regulated in the marriage law.The results of the investigation into this problem were the result of the law of canceling polygamousmarriages for the second ex-wife only in the form of the cancellation of the polygamous marriage. But thereare no legal consequences for the rights of the second ex-wife, none of the laws and regulations in Indonesiaregulate this issue. According to article 28D of the Constitution of 1945, the second ex-wife has the right toobtain justice. The country is immediately guided to form a new rule to regulate the rights and obligations ofthe second ex-wife. Because there are no rules that apply, the second ex-wife can make legal efforts throughnon-court cases in the form of negotiation and mediation or take legal action through legal proceedings inthe form of a civil claim for compensation against the former spouse of a polygamous marriage that wascanceled.Keywords: Marriage - Cancellation - the second wife - right